2019
DOI: 10.1101/mcs.a004085
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal diabetes mellitus due to a novel variant in the INS gene

Abstract: Neonatal diabetes mellitus (NDM) is a rare condition that presents with diabetes in the first few months of life. The treatment of NDM may differ depending on the genetic etiology, with numerous studies showing the benefit of sulfonylurea therapy in cases caused by mutations in KCNJ11 or ABCC8 . Mutations in the insulin gene ( INS ) have also been identified as causes of NDM; these cases are generally best treated with insulin alone. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…From the literature, Laurenzano et al, in 2019, detected a P9R missense variant of the INS gene in a patient, which occurs in the signal peptide of the preproinsulin molecule in an amino acid residue that is highly conserved [32]. Also, the results of Balboa et al, in 2018, demonstrated that neonatal diabetes-associated INS mutations lead to defective beta-cell mass expansion, leading to diabetes development [9].…”
Section: Discussionmentioning
confidence: 99%
“…From the literature, Laurenzano et al, in 2019, detected a P9R missense variant of the INS gene in a patient, which occurs in the signal peptide of the preproinsulin molecule in an amino acid residue that is highly conserved [32]. Also, the results of Balboa et al, in 2018, demonstrated that neonatal diabetes-associated INS mutations lead to defective beta-cell mass expansion, leading to diabetes development [9].…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be explained as the introduction of an additional cysteine may result in misfolding and/or aggregation. The p.P9R ( c.26C>G ) and p.L14R are signal peptide mutations cited as a cause of NDM through β-cell dysfunction, likely due to the introduction of a large and positively-charged arginine residue, in place of a comparatively smaller proline, that confers conformational rigidity and a hydrophobic non-polar leucine residue, respectively [ 4 , 46 ]. Although p.A2T does not affect preproinsulin translocation, it impairs signal peptide cleavage and thus, prevents the production of proinsulin, resulting in MODY type 10 [ 47 ].…”
Section: Insulin Gene Mutationsmentioning
confidence: 99%